2018
DOI: 10.1101/gad.317354.118
|View full text |Cite
|
Sign up to set email alerts
|

Merlin/ERM proteins regulate growth factor-induced macropinocytosis and receptor recycling by organizing the plasma membrane:cytoskeleton interface

Abstract: The architectural and biochemical features of the plasma membrane are governed by its intimate association with the underlying cortical cytoskeleton. The neurofibromatosis type 2 (NF2) tumor suppressor merlin and closely related membrane:cytoskeleton-linking protein ezrin organize the membrane:cytoskeleton interface, a critical cellular compartment that both regulates and is regulated by growth factor receptors. An example of this poorly understood interrelationship is macropinocytosis, an ancient process of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 76 publications
4
47
0
Order By: Relevance
“…The present work suggests that activating mutations of Akt, and possibly SGK, could drive macropinocytic feeding in mammalian cells, increasing the size of macropinosomes and hence nutrient acquisition. Consistent with this hypothesis, recent studies have shown Akt to be activated at sites of macropinocytosis, while inhibition of macropinocytosis inhibits Akt activation (Chiasson-MacKenzie et al, 2018; Erami et al, 2017; Yoshida et al, 2018). Akt inhibition does not depress macropinosome formation in macrophages, although these studies did not rule out smaller macropinosomes and reduced fluid uptake (Pacitto et al, 2017; Yoshida et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…The present work suggests that activating mutations of Akt, and possibly SGK, could drive macropinocytic feeding in mammalian cells, increasing the size of macropinosomes and hence nutrient acquisition. Consistent with this hypothesis, recent studies have shown Akt to be activated at sites of macropinocytosis, while inhibition of macropinocytosis inhibits Akt activation (Chiasson-MacKenzie et al, 2018; Erami et al, 2017; Yoshida et al, 2018). Akt inhibition does not depress macropinosome formation in macrophages, although these studies did not rule out smaller macropinosomes and reduced fluid uptake (Pacitto et al, 2017; Yoshida et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…The resulting vacuolar structure is called the macropinosome, which exhibits no apparent coating structure and is usually larger than 200 nm in diameter [ 90 ]. In turn, macropinocytosis readily provides an efficient, non-specific sampling of the extracellular environment that may contribute to the regulation of cellular dynamics [ 91 , 92 ].…”
Section: Enhancing Ion Internalizationmentioning
confidence: 99%
“…We found some colocalization between fluorescein isothiocyanate (FITC)‐labeled ZNPs and caveolin staining patterns, suggesting that FITC‐ZNPs may undergo caveolin‐mediated endocytosis (Figure C). In addition, as the primary endocytosis pathway for aggregated particles, macropinocytosis was also examined using rhodamine‐labeled dextran (Rhod‐dextran, 70 kD), which enters cells exclusively via macropinocytosis . FITC‐ZNPs were observed in Rhod‐dextran‐containing vacuoles, suggesting that macropinocytosis may be another endocytosis pathway for FITC‐ZNPs (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, as the primary endocytosis pathway for aggregated particles, macropinocytosis was also examined using rhodamine-labeled dextran (Rhod-dextran, 70 kD), which enters cells exclusively via macropinocytosis. [24,25] FITC-ZNPs were observed in Rhod-dextrancontaining vacuoles, suggesting that macropinocytosis may be another endocytosis pathway for FITC-ZNPs ( Figure 1C).…”
Section: Ion Shedding Plays a Crucial Role In The Biological Effectsmentioning
confidence: 95%